Analisis Kesalahan Berbahasa dalam Menulis Teks Non Akademik pada Mahasiswa BIPA di Jambi - Rahmawati, Sophia; Bambang, Siti Enik Mukhoiyaroh (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2024)
Abstract This research aims to analyze the language errors of BIPA students in Jambi Province in writing non-academic texts. The research method used in qualitative research is a content analysis approach. The data in this research consists of analysis of language errors in the aspects of grammar, vocabulary, spelling, as well as inappropriate cohesion and coherence in the non-academic texts of BIPA students in Jambi City. The source of research data was obtained from written results in the from of proposal texts for BIPA student activities based on the Affiliate Program for BIPA students from Jambi University and Sulthan Thaha Saifuddin Jambi State Islamic University with a total of thirty foreign students from Malaysia and Thailand. The research results show that BIPA students’ language errors consist of errors in grammar, vocabulary, spelling, cohesion and coherence. The causes of these errors are influenced by mother tongue interference, lack of understanding of Indonesian language rules, and communication strategies. This research serves as a guideline for improving BIPA teaching methods to improve Indonesian language skills needed in the ability to write non-academic texts in the form of activity proposals.